Cross Talk between the Calcium-Sensing Receptor and the Vitamin D System in Prevention of Cancer - Aggarwal, Abhishek; Kállay, Enikö (Frontiers in Physiology, 2016)
There is epidemiological evidence for the cancer preventive effect of dietary calcium (Ca2+) and vitamin D. This effect is strongest in colorectal cancer (CRC). The active vitamin D metabolite, 1,25-dihydroxyvitamin D3 (1,25D3), bound to its receptor, the vitamin D receptor (VDR) regulates the expression of hundreds of different genes in a cell- and tissue-specific manner. While Ca2+ acts through multiple mechanisms and pathways, some of its effects are mediated by the calcium-sensing receptor (CaSR). The joint action of Ca2+ and 1,25D3 is due to the fact that both regulate some of the main processes involved in the development of various cancers, such as proliferation, differentiation, apoptosis, migration, and inflammation. Moreover, 1,25D3, bound to VDR can induce translation of the CaSR, while the amount and activity of the CaSR affects 1,25D3 signaling. However, the complexity of the cross-talk between the CaSR and the vitamin D system goes beyond regulating similar pathways and affecting each other's expression. Our aim was to review some of the mechanisms that drive the cross-talk between the vitamin D system and the CaSR with a special focus on the interaction in CRC cells. We evaluated the molecular evidence that supports the epidemiological observation that both vitamin D and calcium are needed for protection against malignant transformation of the colon and that their effect is modulated by the presence of a functional CaSR.